Plant Regeneration in Buckwheat (Fagopyrum esculentum Moench.) via Somatic Embryogenesis and Induction of Meristemoids in Abnormal Embryos (Plant Tissue Culture and Biotechnology, 2019)
An efficient in vitro regeneration protocol is reported for common buckwheat. A combination of 0.5 mg/l 2,4-D and 0.2 mg/l BAP with sucrose showed highest induction of somatic embryogenesis from cotyledon and hypocotyl explants. More than 35% of normal somatic embryos matured on MS. MS with 2% sucrose were found best for germination and conversion of somatic embryos to plantlets. In tissue culture, abnormal somatic embryos usually occur. In this report, abnormal embryos are also used to induce shoot organogenesis, adding to the number of final regenerants and ensuring full utilization of regenerative propagules. A treatment of 0.2 mg/l BAP induced meristemoids in 60% of underdeveloped embryos and a combination of 0.5 mg/l BAP and 0.5 mg/l AgNO3 led browning and senescence-free progression of shoot buds to well developed shoots, which were subsequently rooted in half strength MS containing 2% sucrose and 0.25 mg/l IBA. The regenerated plants survived acclimatization, flowered and set seeds.Plant Tissue Cult. & Biotech. 29(1): 33-47, 2019 (June)